Covid-19 Perception: A Survey in Kano Metropolis, Nigeria - Zunaidah, Sulong; Ibrahim, Farouq; Nuraddeen, Umar Sambo (2020)
The primary focus of this study is to examine the psychological perception of individuals towards Covid-19 in Kano metropolitan City of Nigeria, and how it affects their income level. This analysis uses a descriptive quantitative research approach and, as per Sutton, a descriptive analysis produces both primary and secondary data. It was further emphasized that descriptive analysis uses experimental observation to assess and identify what has been observed. In this study, we further use the proportional sampling technique. We conducted the survey in the seven-metropolitan city of Kano State, Nigeria, given their diverse socio-economic status. The estimated total number of populations is 3,999,000. Using the Krejcie-Morgan table, 384 sample size was suggested, however, there was a provision for the unexpected, as such we distributed 400 questionnaires. The findings showed that there were 91.2% respondents who did not perceive Covid-19 pandemic as something to be psychologically worried about. Likewise, 91.1 percent of the respondents have answered not really anxious or feel not comfortable about the issue of Covid-19 pandemic, and lastly, 91.2 percent of the respondents answered not depressed about the situation in any way.